Shear strength and stress-strain characteristics of Diliman silts - Adajar, Joash Bryan Q.; Molina, Ivan B.; Zarco, Mark Albert H. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
This study aims to obtain the fundamental properties of Diliman Silt, to verify its soil classification, and primarily to determine its shear strength and stress-strain behavior. Preliminary tests - including sieve and hydrometer analyses, Standard Proctor tests for compaction, and tests for soil fabric, mineral composition, Atterberg limits, and specific gravity - are performed for soil classification and sample reconstitution. Direct shear tests are performed on consolidated-drained samples reconstituted using Moist Tamping method. All experimental methods are performed under ASTM standards. The effects of varying vertical stress and overconsolidation ratio on the peak and ultimate shear stress, on the cohesion and drained angle of friction, and on the possible occurrence of strain softening are investigated. In cases where no strain softening is observed, the Modified Hyperbolic Model is used to describe the stress-strain behavior using the resulting material parameters obtained from the direct shear tests. The soil is poorly-graded sand (SP) based on USCS, while silty or clayey sand (A-2-6) based on AASHTO. Normally consolidated samples and overconsolidated samples with OCR = 2 experienced no strain softening accompanied by the absence of dilation of the sample throughout the test; thus, these samples exhibit stress-strain behavior that can be reliably predicted by the Modified Hyperbolic Model. The rest of the overconsolidated cases dilated more with increasing OCR, inferring that the occurrence of strain softening becomes more probable in these cases.
Thesis (B.S. Civil Engineering)--University of the Philippines Diliman
Keywords: Silt; Shear strength of soils; Strains and stresses